Onychomadesis in a child with spinal muscular atrophy type I. - Ruggiero, G. (European Journal of Pediatric Dermatology, 2006)
A case of Werdnig-Hoffmann disease or spinal muscular atrophy in a 4-year-old child is reported. At this age the child presented onychomadesis of both halluces leading to the elimination of the distal fractured nail lamina within 8 months. Initially, a possible damage on the matrix induced by the saturimeter was hypothesized and led to move the latter from the halluces to the plantar region. However, onychomadesis relapsed on the right hallux a year after the suspension of contact with the saturimeter, ruling out this hypothesis. After having excluded infectious and traumatic causes, an idiopathic form possibly associated to spinal muscular atrophy was diagnosed.